Meta-analysis of environmental effects of beaver in relation to artificial dams. (8th November 2017) - Ecke, Frauke; Levanoni, Oded; Audet, Joachim; Carlson, Peter; Eklöf, Karin; Hartman, Göran; McKie, Brendan; Ledesma, José; Segersten, Joel; Truchy, Amélie; Futter, Martyn
Abstract: Globally, artificial river impoundment, nutrient enrichment and biodiversity loss impair freshwater ecosystem integrity. Concurrently, beavers, ecosystem engineers recognized for their ability to construct dams and create ponds, are colonizing sites across the Holarctic after widespread extirpation in the 19th century, including areas outside their historical range. This has the potential to profoundly alter hydrology, hydrochemistry and aquatic ecology in both newly colonized and recolonized areas. To further our knowledge of the effects of beaver dams on aquatic environments, we extracted 1366 effect sizes from 89 studies on the impoundment of streams and lakes. Effects were assessed for 16 factors related to hydrogeomorphology, biogeochemistry, ecosystem functioning and biodiversity. Beaver dams affected concentrations of organic carbon in water, mercury in water and biota, sediment conditions and hydrological properties. There were no overall adverse effects caused by beaver dams or ponds on salmonid fish. Age was an important determinant of effect magnitude. While young ponds were a source of phosphorus, there was a tendency for phosphorus retention in older systems. Young ponds were a source methylmercury in water, but old ponds were not. To provide additional context, we also evaluated similarities and differences between environmental effects of beaver-constructed and artificial dams (767 effect sizes from 75 studies). Both are comparable in terms of effects on, for example, biodiversity, but have contrasting effects on nutrient retention and mercury. These results are important for assessing the role of beavers in enhancing and/or degrading ecological integrity in changing Holarctic freshwater systems.